Remote sensing for urban heat and cool islands evaluation in semi-arid areas - M. Reisi; M. Ahmadi Nadoushan; L. Aye (Global Journal of Environmental Science and Management)
Cities are experiencing rapid population growth and consequently extensive urbanization. Land-use/land-cover change is one of the important elements worldwide, which significantly affect the environment. This study aims to describe the emergence of urban heat and cool islands as a result of changes in land-use/land-cover. Land surface temperature over a 32-year period in Isfahan city, Iran was retrieved. The results confirmed the effect of land-use/land-cover change on Landsat land surface temperature. The average land surface temperature changed from 37.5°C in 1985 to 42.7°C in 2017 during August. The highest land surface temperature in the study area for both years occurred on bare soils (40.66°C in 1985 and 45.88°C in 2017). The second highest Landsat land surface temperature was recorded in central parts of the city with dense built-up covers (36.93°C in 1985 vs 42.45°C in 2017). The central parts of the city were found to have a lower Landsat land surface temperature compared to bare soils, which contributes to the formation of urban cool islands. As expected, water bodies and vegetation had a lower Landsat land surface temperature compared to other land covers. The results also showed changes in land use types during 1985 and 2017, with an increase in water bodies (148.82%) and built-up areas (39.67%) and a decrease in vegetation (20.08%) and bare soil (12.42%). The areas converted from vegetation to built-up experienced an increase in Landsat land surface temperature, which confirmed the effect of land-use/land-cover on microclimate.